Tristão e Isolda no sertão: dialogismo e adaptação no filme Romance, de Guel Arraes // Tristan and Isolde in the hinterland: dialogism and adaptation in the film Romance, by Guel Arraes - Barbosa, Afonso; Mousinho, Luiz Antonio (Contemporanea, 2016)
We aim to analyse the film Romance, by Guel Arraes, observing its intertextual relations from the standpoint of Bakhtin’s dialogism. We are going to investigate these processes from Robert Stam studies within literature and cinema, in addition to examining data from the adaptation context also expounded by this researcher. We also analyse the characterization of the characters and the connections established between the film and other literary narratives and dramatic texts.